Research that matters: Outcome mapping for linking knowledge to poverty-reduction actions - Nyangaga, J.; Smutylo, T.; Romney, Dannie L.; Kristjanson, Patricia M. (Informa UK Limited, 2010)
An 'Outcome Mapping' approach was applied retrospectively to five diverse, highly collaborative research projects aimed at poverty reduction. Designed to help plan for, clarify, and document intended and actual changes in behaviour, actions, and relationships of groups and organisations that directly influence a project's intended beneficiaries, Outcome Mapping enabled us to identify and describe the strategies and actions that played important roles in the innovations achieved. Successful strategies observed included the use of champions, jointly producing high-profile outputs that enhanced the status of local partners, multiple communication strategies, targeting ongoing policy processes, and strong emphases on and investment in capacity building.